KETEPATAN SASARAN DANA BOS BAGI SISWA SMP NEGERI DI KOTA MAKASSAR - Irawati, Irawati; Kara, Muslimin; Umar, Mustofa (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2019)
The School Operational Assistance Program is a form of government compensation for reducing subsidy funds for fuel oil in order to increase the demand of the poor for education services. This study aims to analyze the progressiveness of the School Operational Assistance Program for Public Junior High Schools in Tamalate District, Makassar City. This research was conducted using Benefit Incidence Analysis (BIA) analysis method. This research was conducted at SMPN 15 Makassar, SMPN 18 Makassar, SMPN 24 Makassar, SMPN 26 Makassar and SMPN 27 Makassar in February 2017. Data collection in the study used survey method through questionnaires distributed to students in the sample schools. The results of this study indicate that the School Operational Assistance Program for Public Junior High Schools in Tamalate District, Makassar City is a progressive policy that provides benefits of more than 30% to the poor.